Law's response to New Zealand's 'darkest of days'. (March 2021) - Ip, John
This article discusses various aspects of the New Zealand legal system's response to the 15 March Christchurch mosques attack. It also considers New Zealand's response to the attack from the perspective of the academic literature on the policymaking process and argues that the response to date has been modest and cannot be characterised as a knee-jerk reaction.